KLF5 silencing restrains proliferation, invasion, migration and angiogenesis of gallbladder carcinoma cells by transcriptional regulation of PDGFA - Xiaowei Lu; Kui Hu; Dandan Zhang; Xuefeng Yin; Jifeng Nie; Kai Zhao (Journal of Cancer Research and Clinical Oncology)
Abstract Background Krüppel-like factor 5 (KLF5) is recognized as a tumor mediator in multiple types of tumors. Nevertheless, whether KLF5 plays a role in gallbladder cancer (GBC) remains to be elucidated. This study aims to clarify the role of KLF5 in the proliferation, migration and angiogenesis in GBC cells. Methods The expressions of KLF5 and platelet-derived growth factor subunit A (PDGFA) in GBC cell lines were analyzed by qRT-PCR and western blot assay. Cell proliferation was assessed utilizing the Cell Counting Kit-8 assay and EDU staining. Cell apoptosis was evaluated using flow cytometry, and apoptosis-related proteins was examined by western blotting. The migratory and invasive capabilities were evaluated utilizing wound healing and Transwell. Angiogenesis was assessed by ELISA, tube formation assay and western blot. The interaction between KLF5 and PDGFA was confirmed by ChIP assay, as well as luciferase reporter assay. Results In this study, we discovered that the levels of KLF5 and PDGFA were upregulated in GBC cells. Silencing of KLF5 reduced the viability and suppressed the proliferation of GBC cells, as well as promoting the apoptosis. In addition, KLF5 silencing restrained the invasion and migration and angiogenesis in NOZ and GBC-SD cells. KLF5 transcription activated PDGFA expression and KLF5 was proved to bind to PDGFA promoter in NOZ cells. Following the silencing of PDGFA, the proliferation, invasion, migration, angiogenesis and apoptosis exhibited similar changes to KLF5 silencing. Additionally, PDGFA overexpression reversed the effects of KLF5 silencing on NOZ cells. Conclusion Collectively, our results suggest that KLF5 regulates GBC cell proliferation, invasion, migration, angiogenesis, as well as apoptosis, via mediating PDGFA transcriptionally, which might provide a novel therapeutic strategy for treatment of human GBC.